Emergency Liquidity Support Facilities - He, Dong (IMF Working Papers; Working Paper, 2000)
This paper discusses operational aspects of official emergency liquidity support to individual institutions under stress. It argues that properly designed lending procedures, clearly laid-out authority and accountability, as well as disclosures rules, will promote financial stability, reduce moral hazard, and protect the lender of last resort from undue political pressure. Although there may well be good reasons to maintain ambiguity over the conditions for assistance, there are important advantages for developing, and for transition economies to follow a rule-based approach by setting out ex ante the necessary conditions for support, while maintaining that meeting such conditions is not sufficient for receiving support.